Indigenous University Student Persistence: : Supports, Obstacles, and Recommendations - Walton, Patrick D; Hamilton, Kristen; Clark , Natalie; Pidgeon, Michelle; Arnouse, Mike (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
The tumultuous history of Indigenous education in Canada has negatively affected the persistence of Indigenous peoples at university. The research goals of this study were to identify the key supports and obstacles related to Indigenous university student persistence and to make recommendations as to how to improve levels of persistence. Combining interview, survey, and database information with 527 Indigenous students revealed that the strongest factors related to persistence were (a) social engagement, including good relationships with faculty and students, and support services provided by the Indigenous gathering place for Indigenous students on campus; (b) cognitive, such as academic support at university, learning effectively on their own, and hands-on teaching; (c) physical, including insufficient financial support and availability of affordable housing and child care; and (d) cultural, including connections with Indigenous faculty and culture. Age, home location, and parental education were not found to be related to persistence. Keywords: Indigenous, Aboriginal, persistence, university, graduation, Indigenous student experience, Canada